Effect of cryogenic cooling on machinability and surface quality of bio-degradable ZK60 Mg alloy. (15th December 2015) - Dinesh, S.; Senthilkumar, V.; Asokan, P.; Arulkirubakaran, D.
Abstract: Lubrication and cooling during machining processes have critical impact on the desired quality of final product through control of friction and heat generation. Application of cryogenic liquids as coolant during machining improves the surface characteristics of newly formed machined surface. In addition to the cooling of work piece and tool surfaces, they act as effective lubricant between contact surfaces. Turning experiments on ZK60 magnesium alloys samples were conducted under various cutting speed and feed rate in the present investigation. Influence of liquid nitrogen during machining on cutting temperature, cutting forces, hardness, surface roughness and microstructural evolution was investigated. The effect of cryogenic cooling on heat affected zone, formation of precipitates and grain size was also studied. Beneficial effects of cryogenic cooling over dry machining such as reduction in cutting temperature and cutting forces, improvement in surface finish and hardness were observed. Moreover, cryogenic machining improved the intensity of basal crystallographic plane and initiated the formation of a featureless layer. Graphical abstract: Highlights: Liquid nitrogen was used as coolant–lubricant during turning process. Reduction in cutting temperature and cutting forces were observed in cryogenic machining over that of dry machining. Improved surface hardness and enhanced surface finish of machined samples were witnessed in cryogenic machining. Increment in intensity of basal crystallographic plane (0002) was observed under cryogenic machining. A featureless layer of 30 μm from the machined surface to subsurface were observed.